2017
DOI: 10.1177/1550059417742297
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Impulsive Error in Children With ADHD

Abstract: A deficit of inhibition ability is a neuropsychological problem in children with attention deficit hyperactivity disorder (ADHD). We investigated whether in children who made impulsive error (IE), less error-related negativity (ERN) would correlate with poorer executive attention functions (EAFs). Ninety children (49 with ADHD and 41 without ADHD) were investigated by a 4-minute simple reaction time task and simultaneous electroencephalogram. When they made IE, the ERN in response-locked event-related potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Two novel ADHD groups were created: one with reduced ERN amplitudes (n=26) and one with ERN amplitudes comparable to controls (n=5). Only the reduced-ERN subgroup had poorer performance on the Comprehensive Nonverbal Attention test, an objective measure of executive function, although both groups provided equivalent subjective ratings of executive function (Liao et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two novel ADHD groups were created: one with reduced ERN amplitudes (n=26) and one with ERN amplitudes comparable to controls (n=5). Only the reduced-ERN subgroup had poorer performance on the Comprehensive Nonverbal Attention test, an objective measure of executive function, although both groups provided equivalent subjective ratings of executive function (Liao et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Five of the ten studies used previously-identified EEG markers to create ADHD subgroups, and then assessed differences in EEG or behavioral measures between the subgroups. Four studies used spectral analysis of resting state EEG and one study defined subgroups based on the error-related negativity (ERN) during a reaction time task (Liao et al, 2018). All five studies included children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Performance and monitoring abilities are also deficient in ADHD children and adolescents in executive attention and flanker tasks. 17,18 Their frontal beta-band activities cannot be enhanced when task complexity increases. 19…”
Section: Introductionmentioning
confidence: 99%
“…16 Performance and monitoring abilities are also deficient in ADHD children and adolescents in executive attention and flanker tasks. 17,18 Their frontal beta-band activities cannot be enhanced when task complexity increases. 19 Many meta-analysis studies that have reviewed neurofeedback treatment in ADHD have shown the short-term and follow-up effects in the symptoms of ADHD [20][21][22] Standard neurofeedback training protocols, including TBR, sensorimotor rhythm(SMR), and slow cortical potential(SCP), have been considered viable treatment alternatives for ADHD [21][22][23] Indications are that neurofeedback can find considerable utility as an intervention strategy in academic settings for individuals with ADHD.…”
Section: Introductionmentioning
confidence: 99%